PTU-091 Anti-tnf Therapy Reduces Ionising Radiation Exposure In Patients With Crohn's Disease. (9th June 2014) - Aggarwal, D; Limdi, JK
Abstract : Introduction: Patients with Crohn's Disease [CD] are often exposed to ionising radiation for the diagnosis and evaluation of disease with inherent risks from protracted exposure. Meanwhile, bolder definitions of disease control have changed treatment paradigms with earlier introduction of biological therapy in many. Our aim was to compare the effective radiation dose a year prior and 1 and 3 years after initiating anti-TNF therapy or corticosteroid. Methods: We performed a retrospective review of CD patients treated with anti-TNF (infliximab or adalimumab) or corticosteroids at our institution from 2005 to 2013. Clinical data (demographics, disease characteristics, treatment) were obtained from patient records. All instances of imaging in the previous year and 1 and 3 years after initiation of therapy were recorded. Effective and cumulative radiation doses were calculated from published tables [Royal College of Radiologists, UK]. Results: We analysed 170 patients with CD (114 anti-TNF, 56 corticosteroid). In the anti-TNF group, 55% were female (median age 35 yrs;mean disease duration 8.2yrs). Disease location was ileal (46%), colonic (21%), ileocolonic (31%) and perianal (22%) with inflammatory, stricturing and penetrating disease in 63%, 14% and 23% respectively. In the corticosteroid group, 53% were females (median age 48; mean disease duration 13.2yrs). Disease location was ileal (44%), colonic (27%), ileocolonic (29%) and perianal (14%) with inflammatory, stricturing and penetrating disease in 75%, 20% and 5% respectively. The anti-TNF cohort had a significant reduction in the cumulative radiation dose (4.2 vs. 1.8 mSv, p < 0.0001) compared to the previous year. There was no change in the cumulative radiation dose in the corticosteroid group (7.5 vs.7.3 mSv, p = 0.8). The number of CT scans reduced from 3.3 to 1.2 (p < 0.0001) in the anti-TNF cohort. There was no reduction the number of CT scans in the corticosteroid group after one year (2.7 vs . 2.5, p = 0.006). In 31 patients with 3-year exposure to corticosteroids, there was a significant increase in the cumulative radiation dose (7.0 vs. 13.8 mSv, p < 0.0003) compared to the anti-TNF group (3.5 vs. 4.8 mSv, p = 0.7). There was a significant increase in the number of CT scans in the corticosteroid group (2.6 vs. 4.9, p < 0.001) compared to the anti-TNF group (2.5 vs . 2.8, p = 0.9). Linear regression analysis showed a decrease in cumulative radiation dose by 2.7 mSv (p = 0.07) and number of CT scans by 2 (p < 0.001) in the anti-TNF group compared to the corticosteroid group within a year of therapy after adjusting for age, gender, disease duration, disease location and disease behaviour. Conclusion: Anti-TNF but not corticosteroid therapy is associated with a significant reduction in diagnostic radiation exposure a year after treatment and persisted after 3 years although not statistically significant Disclosure of Interest: None Declared.